Level of Mental Well-being among Education Students: Basis on the Development of Awareness Campaign (Synergy: Cross-Disciplinary Journal of Digital Investigation (2995-4827), 2023)
The primary purpose of this study was to assess college students’ level of mental well-being, which served as the foundation for developing ‘Flyer/Pamphlet' as awareness campaign material for Education students of Altavas College. A 25-item survey questionnaire for level of mental well-being collected the data by using an electronic web-based questionnaire through the Google survey tool (Google Forms) and a 20- item checklist questionnaire for level of acceptability was used and self-administered to gather information on the level of acceptability of the respondents. Data obtained were analyzed and assessed using frequency count, percentage, and mean. Results showed that the level of mental well-being of Education students at Altavas College was ‘moderately assured’. In line with this, the most appropriate product to be developed based on the results of the study was a Flyer/Pamphlet for Education students of Altavas College. The developed awareness campaign material which is the Flyer/Pamphlet was then evaluated with a ‘very highly acceptable’ level of acceptability in terms of content, coherence, and clarity; appeal to the target audience; functionality; and its overall mean findings. This concludes that the Flyer/Pamphlet as an awareness campaign material highly satisfied the criteria for a profound and high-quality resource that can be used by students in promoting and improving their mental well-being.